Molecular Trajectory of BRCA1 and BRCA2 Mutations - Hatano, Yuichiro; Tamada, Maho; Matsuo, Mikiko; Hara, Akira (Frontiers in Oncology, 2020)
Every cancer carries genomic mutations. Although almost all these mutations arise after fertilization, a minimal count of cancer predisposition mutations are already present at the time of genesis of germ cells. Of the cancer predisposition genes identified to date, BRCA1 and BRCA2 have been determined to be associated with hereditary breast and ovarian cancer syndrome. Such cancer predisposition genes have recently been attracting attention owing to the emergence of molecular genetics, thus, affecting the strategy of cancer prevention, diagnostics, and therapeutics. In this review, we summarize the molecular significance of these two BRCA genes. First, we provide a brief history of BRCA1 and BRCA2, including their identification as cancer predisposition genes and recognition as members in the Fanconi anemia pathway. Next, we describe the molecular function and interaction of BRCA proteins, and thereafter, describe the patterns of BRCA dysfunction. Subsequently, we present emerging evidence on mutational signatures to determine the effects of BRCA disorders on the mutational process in cancer cells. Currently, BRCA genes serve as principal targets for clinical molecular oncology, be they germline or sporadic mutations. Moreover, comprehensive cancer genome analyses enable us to not only recognize the current status of the known cancer driver gene mutations but also divulge the past mutational processes and predict the future biological behavior of cancer through the molecular trajectory of genomic alterations.